IMPLEMENTASI PROGRAM BEEPREENEUR CILIK PADA PEMBELAJARAN IPAS MATERI EKOSISTEM DENGAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING DI SDN MEKAR SARI - Raudah; Naila Aziza; Jum’ah; M. Amien; Diani Ayu Pratiwi; Yenny; Mellan Yuliastina; Muhammad Baihaqi; Asih Fuji Rahayu; Desy Mayang Sari; Reva Rizkya Febrina; Joice Stephanie (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the problem of abstract and textbook-centered IPAS learning in elementary schools, which results in low conceptual understanding and learning achievement, particularly in ecosystem topics. The study aims to examine the implementation of ecosystem learning based on Contextual Teaching andLearning (CTL), supported by the Teams Games Tournament (TGT) strategy and integrated with the Beepreneur Cilik program at SDN Mekar Sari. This research employed a qualitative descriptive approach conducted during the 2025 Thematic Community- Based Student Program of Universitas Lambung Mangkurat. Data were collected through observation, interviews, documentation, and supported by pre-test and post-test results. The findings showed a significant improvement in students’ learning outcomes, with mastery learning increasing from 32% to 100%. Students demonstrated better understanding of ecosystem components, the ecological role of kelulut bees, and environmental sustainability. The integration of entrepreneurship activities also enhanced students’ creativity and environmental awareness. These results indicate that contextual IPAS learning integrated with local potential is effective and meaningful for elementary students.